2009
DOI: 10.3136/fstr.15.449
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Lutein in Chlorella Powder: A Single Ingestion of Chlorella Powder Raises Serum Lutein Concentrations in Healthy Human Volunteers

Abstract: Chlorella powder (CP), a dietary supplement made from a green alga, contains abundant lutein (2.8 mg/g), but the bioavailability of lutein in CP has not been evaluated. In the present study, we assessed the effect of a single ingestion of CP (3 or 6 g) in tablet form on serum lutein concentrations in humans (n = 21). At 1 d, serum lutein concentrations increased from baseline values by 34% (25.6 nM/mg-lutein intake) after 3 g CP and by 66% (21.4 nM/mg-lutein intake) after 6 g CP. These results suggest that lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Results showed that for all carotenoids, the values of AUC and C max were significantly different from zero ( p < 0.01), indicating that a single dose of marine Chlorella vulgaris (6 g) increased plasma concentrations of lutein, β-carotene and zeaxanthin in healthy subjects. For lutein, the major carotenoid identified in marine Chlorella vulgaris ( Table 2 ), the C max achieved in this study per mg of ingested lutein (2.88 µg·L −1 ) was lower than the value reported by Shibata and Hayakawa (7.23 µg·L −1 ) [ 24 ], and this difference could be explained by the absence of olive oil in the meal. When compared with other food matrices rich in lutein, the range of C max obtained herein per mg of lutein intake (0.7–12.2 µg·L −1 ) are within the values reported for a dose of broccoli (200 g) (5.0 µg·L −1 ) and spinach (150 g) (10.5 µg·L −1 ) [ 27 ].…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Results showed that for all carotenoids, the values of AUC and C max were significantly different from zero ( p < 0.01), indicating that a single dose of marine Chlorella vulgaris (6 g) increased plasma concentrations of lutein, β-carotene and zeaxanthin in healthy subjects. For lutein, the major carotenoid identified in marine Chlorella vulgaris ( Table 2 ), the C max achieved in this study per mg of ingested lutein (2.88 µg·L −1 ) was lower than the value reported by Shibata and Hayakawa (7.23 µg·L −1 ) [ 24 ], and this difference could be explained by the absence of olive oil in the meal. When compared with other food matrices rich in lutein, the range of C max obtained herein per mg of lutein intake (0.7–12.2 µg·L −1 ) are within the values reported for a dose of broccoli (200 g) (5.0 µg·L −1 ) and spinach (150 g) (10.5 µg·L −1 ) [ 27 ].…”
Section: Resultscontrasting
confidence: 80%
“…The bioavailability of carotenoids from a single dose of Chlorella vulgaris in humans was only reported by Shibata and Hayakawa, who demonstrated that 3 g or 6 g of this microalga increased the serum concentration of lutein by up to 66% for 3 days after the intake [ 24 ]. The high serum lutein concentration observed could be related to the simultaneous administration of olive oil, which has already been described to improve the intestinal bioaccessibility, absorption kinetics and bioavailability of carotenoids in vivo [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorella algae contains high amounts of lutein 11 , and a previous study suggested that Chlorella intake influences serum lutein levels 12 . With a single oral dose of Chlorella a 6 g Chlorella tablet, containing 15 mg lutein , serum lutein concentration reportedly increased about one and a half-fold, but erythrocyte lutein concentrations were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Table 2 . Considering the results of previous studies 12,18,19 and our findings Fig. 1 and Table 2 , daily intake of Chlorella leads to increased plasma lutein in normal subjects.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation